The Effectiveness of Hydrogel from Snakehead Fish Extract (Chana Striata) on Wound Healing of Grade II Ulcer in Type II Diabetes Mellitus Patients - Pratiwi; Suharyo Hadisaputro; Sudirman; Ta'adi; Lanny Sunarjo (Alta Dharma Publisher, 2021)
Diabetic ulcers are complications of diabetes mellitus. The prevalence of diabetic ulcers was 15%from the total population. Effective management of ulcers using an antiseptic could interfere with the wound healing process. A hydrogel from snakehead fish extract was a complementary treatment to improve the wound healing of diabetes. The study aimed to examine hydrogel's effectiveness from snakehead fish extract on wound healing among type II diabetes mellitus with grade II ulcers. The quasi-experimental study, pretest, and post-test with the non-equivalent control group were applied in this study. The intervention group (n = 16) received a dose of 675.675 mg of snakehead hydrogel and 0.9% NaCl for 21 days. The control group (n = 16) only received 0.9% NaCl. Analysis with repeated ANOVA test and Dependent t-Test was applied in this study. The results showed that the intervention group's mean score for wound healing before receiving the intervention was 26.31 ± 6.740after 14 days receiving the intervention was 13.00 ± 4.872 with p-value = 0.000. The mean difference between the intervention group and the control group also showed the mean was346.25 more than the control group with a delta score of 301.31. In conclusions showed that hydrogel extract of snakehead fish was effective among type II diabetes mellitus patients with healing grade II ulcers